PEMAHAMAN TENTANG PRASARANA PERKERETAAPIAN GUNA PENINGKATAN KESIAPAN KERJA LULUSAN SMK - Kurniawan, Muhammad Adib; Puspita Dewi; Wawan Riyanta; Dimas Adi Perwira; Armyta Puspitasari (Madiun Spoor : Jurnal Pengabdian Masyarakat, 2023)
In accordance with the National Education System Law No. 20 of 2003, article 3 concerning National Education Goals and explained in article 15 that vocational education is secondary education that prepares students especially to work in certain fields which means that Vocational High Schools (SMK) aim to prepare graduates who are ready to work[1][2]. Job opportunities in the world of railways are very large, so it is necessary to provide initial or basic knowledge related to railway infrastructure, especially buildings and railway lines, to prospective graduates of the Central Java State Vocational School in Semarang in the field of Construction and Property Business expertise so that they have more knowledge in the field of railways as a provision to enter the world of work. The results of providing material in the form of Railway Infrastructure Knowledge Technical Guidance found that the technical guidance participants were very enthusiastic and enthusiastic.